FACTORS AFFECTING WORK QUALITY AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Sumarsid Sumarsid; Syech Idrus; Evi Mafriningsianti; Ahmad Rifa’i (Yayasan Education and Social Center, 2023)
Human resources play a very important role in the sustainability of a company or institution. Human resources are responsible for managing and managing all company or institution activities, from planning, organizing, implementing, and supervising. HR is responsible for creating and maintaining a healthy corporate or institutional culture, as well as creating a conducive work environment for all employees. As a research method used the method of observation and observation of PT. XYZ, but the data studied is data that comes from observations and observations are sampled to find relative occurrence, distribution and relationships between variables. In this study the sample consisted of 96 employees who used saturated sample data collection techniques. Research shows that work quality and work motivation have a significant effect on employee performance at the PT. Both work quality and individual work motivation also have a significant influence on employee performance. However, 64.90% other factors outside the research also affect employee performance. Factors that affect the quality of work at the PT include growth and development, participation, reward system innovation, work environment, and welfare. While the factors that influence work motivation on employee performance include salary, working conditions, job opportunities, job performance, management recognition, and the job itself.